2007
DOI: 10.1002/nau.20437
|View full text |Cite
|
Sign up to set email alerts
|

Antidiuresis therapy: Mechanism of action and clinical implications

Abstract: Abnormalities of micturition occur in many different diseases, have a variety of causes and take several forms. This review will focus exclusively on those abnormalities in which antidiuretic therapy may be of benefit. These conditions are primarily characterized by an increase in the total amount of urine produced (polyuria) or a circadian shift in the control of urine production and/or voiding (nocturnal enuresis, nocturia).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 77 publications
(76 reference statements)
0
21
0
Order By: Relevance
“…The result is 24‐hour polyuria and polydipsia, known as diabetes insipidus, which is a rare condition diagnosed via a bladder diary and a low morning (fasting) serum and urine osmolality. An abnormal circadian rhythm of vasopressin is the main mechanism for NP . Asplund described a lack of circadian rhythm in patients with NP and nocturia in both men and women, but plasma levels in adults without nocturia peak at around 8 pg/mL in men and 4 pg/mL in women—both with a circadian rhythm .…”
Section: Resultsmentioning
confidence: 99%
“…The result is 24‐hour polyuria and polydipsia, known as diabetes insipidus, which is a rare condition diagnosed via a bladder diary and a low morning (fasting) serum and urine osmolality. An abnormal circadian rhythm of vasopressin is the main mechanism for NP . Asplund described a lack of circadian rhythm in patients with NP and nocturia in both men and women, but plasma levels in adults without nocturia peak at around 8 pg/mL in men and 4 pg/mL in women—both with a circadian rhythm .…”
Section: Resultsmentioning
confidence: 99%
“…Sleep apnea is known to lead to an increase in atrial natriuretic peptide, resulting in nocturnal natriuresis and consequently increased diuresis (solute diuresis) which does not respond to vasopressin receptor 2 (V 2 ) agonist treatment (desmopressin). 44 A number of studies have shown a decrease in nocturia episodes and/or nocturnal urine production with continuous positive airflow pressure therapy treatment for sleep apnea. 45, 46 In other patients with NP and a dilute diuresis, antidiuretic therapy may be effective.…”
Section: Treatment Of Nocturiamentioning
confidence: 99%
“…45, 46 In other patients with NP and a dilute diuresis, antidiuretic therapy may be effective. Desmopressin is a synthetic analogue of the naturally-occurring antidiuretic hormone, arginine vasopressin, and it has been found to be an effective treatment in nocturia patients, 44 with mean number of voids per night reduced to less than two on average. 47-49 Reductions in nocturia frequency with treatment are accompanied by a significant increase in the hours of undisturbed sleep 50 (Figure 2), and a lengthening of the initial sleep period compared with placebo.…”
Section: Treatment Of Nocturiamentioning
confidence: 99%
“…Moreover, failures of this homeostatic regulation are predicted to negatively affect organisms' well-being. Indeed, nocturia (bothersome waking-up at night to void) are known to decrease quality of life and negatively affect morbidity and mortality in human beings, especially in the elderly [5,6]. Researches also indicated that nocturia disrupts sleep architecture and predicts obstructive sleep apnea while acute sleep deprivation results in excess diuresis and natriuresis [7,8].…”
mentioning
confidence: 99%
“…In these efforts, key molecules linking circadian clock and voiding function should be clarified. Given the multifaceted nature of voiding function and dysfunction [5,9], however, all the possible alternatives need to be considered as well.…”
mentioning
confidence: 99%